Fabrication of lignin-based biochar containing multi-metal ferrite and efficient removal for oxytetracycline hydrochloride. (10th January 2022) - Lin, Huiting; Qiu, Shijie; Wu, Zhihao; Ye, Xiaoxia; Liu, Minghua
Abstract: Efficient removal of oxytetracycline hydrochloride (OTC) from wastewater is of great significance but extremely challenging. Herein, a novel adsorbent lignin-based multi-metal ferrite biochar (FeNiZn-LBC) was synthesized through pyrolysis with controllable temperature and hydrothermal reaction using lignin of sinocalamus oldhami as raw material. The adsorption property of FeNiZn-LBC for OTC was systematically researched, and the results displayed that adsorption of FeNiZn-LBC to OTC accorded with the Langmuir model and the equilibrium adsorption capacity was 476 mg g −1 . Notably, FeNiZn-LBC can be regenerated with 0.100 mol L −1 NaOH. Additionally, we raised rational explanations for the mechanisms of adsorption behavior based on the zeta potential and XPS spectra. The adsorption of FeNiZn-LBC for OTC was mainly controlled by the electrostatic interactions, hydrogen bonds and complexation involving FeNiZn-LBC and OTC, especially the metal-oxide bond (M-O) generated after loaded with multi-metal ferrite played a positive role in the removal of OTC from water. Our work highlighted the potential of FeNiZn-LBC for excellent adsorption of OTC in next generation. Graphical abstract: Image 1 Highlights: The novel adsorbent FeNiZn-LBC shows excellent adsorption efficiency to OTC. The adsorbent was prepared from alkali lignin of sinocalamus oldhami. The FeNiZn-LBC was easily separated from water under external magnetic field. The synergistic effect of multi-metal ferrite provides more adsorption capacity.